How Extraversion, Intensity and Novelty Seeking Explain Smoking Status/A Study of Smokers, Non-Smokers and Social Smokers - Rantzou Eleni-Paraskevi (2014)
Abstract, Introduction, Physical and Mental Consequences of Tobacco, Why Do Individuals Smoke?, Categories Among Smokers, Regular Smokers, Social Smokers, Individual Differences, Models Used to Explore Smokers' Characteristics, Personality Traits and Smoking Status, Other Factors Related to Tobacco Consumption, All-or-None Phenomenon, Sensation Seeking and Sustance Use, Personality and Sensation Seeking as Predictors of Tobacco Consumption, An Explanation Regarding Sensation Seeking and Smoking, Aim, Hypotheses, Methods, Design, Participants, Materials, Procedure, Analytic Strategy, Results, Discussion, Main Findings, Implications of the Findings, Strengths and Limitations of the Study, Further Research, Conclusions, References, Appendices.